PKM UPAYA PENINGKATAN KADAR PROTEIN DAN PRODUKSI PADA USAHA KERUPUK MAJU JAYA UNTUK MENDUKUNG PROGRAM PEMERINTAH DALAM UPAYA MENGETASKAN STUNTING DARI PRODUK IKAN LELE - Hadi Purwanto; Sunanto Sunanto; Ilham Hudi; Asiah Asiah; Siti Nurhaini; Diah Ayu Pramesti (LPPM Universitas Bina Bangsa, 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. The incidence of stunting in children under five can occur due to lack or low quality of protein containing essential amino acids. Based on data obtained from the Kampar district health office, it was found that there was a stunting prevalence of 32.99% (in 2020), in 2021 and a prevalence of 23.07%, and in 2022 there was an increase in prevalence of 25.7%. To support the kampar district government program to eradicate free stanting, catfish village MSMEs process catfish cultivation products into processed catfish crackers. In 100 grams of catfish contains protein 20.0%-46.6% (w/k), fat + 20.8 (w/k), minerals + 14.6% (w/k), water and + 6.81% (w/k). Each part of catfish has nutritional content that can be useful if consumed such as catfish head contains 50.94% protein, meat 17.7%, fish bones have a nutritional content rich in calcium which is 39.24%.Crackers are complementary foods that are favored by children because crackers are foods that have a crunchy and savory texture, besides that crackers can be vasriated such as color, shape and taste. This is what underlies the emergence of new innovations for stunting prevention made from catfish which is rich in protein